Dysfunctional Thoughts and Caregiver Burden in the Caregivers of Patients with Hepatitis C - Yousaf, Aasma; Mukarram, Naima (Applied Psychology Review, 2024)
The current study aimed to identify the thought patterns and caregiver burden of the caregivers of patients with hepatitis C. It was hypothesized that there is likely a relationship between dysfunctional thoughts and caregiver burden, where dysfunctional thoughts are likely to predict caregiver burden in the caregivers of hepatitis C patients. This correlational study was conducted with a sample of (N = 100) caregivers (43 men and 57 women). They were recruited from the government hospitals of Lahore by using the purposive sampling technique. The age range of caregivers was 17 to 65 years and only those who had spent more than 6 hours per day with the patient were included. Caregivers with any previously diagnosed psychological problem were excluded from the study. Their personal information and the patients’ current condition were also noted. Dysfunctional Thoughts about Caregiving Questionnaire and Zarit Burden Interview was used. Dysfunctional thoughts were identified to have a significant negative association with caregiver burden and act as predictors of caregiver burden in the caregivers of patients with hepatitis C and its complications. The findings will be beneficial for reducing the caregivers burden of the patients with any infectious disease.